واقع السياسة الاحترازية للبنوك الجزائرية على ضوء اصلاحات القانون النقدي والمصرفي 23-09 - كبير فراح; مرحوم محمد الحبيب (جامعة الوادي University Of Eloued, 2024)
تهدف الدراسة الى معرفة مدى مواكبة وتطبيق الجزائر لمعايير بازل الاحترازية في ظل آخر الاصلاحات التي قامت بها السلطات العمومية في القطاع المصرفي الجزائري التي تمثلت في اصدار القانون النقدي والمصرفي رقم 23-09 الذي يلغي القانون رقم 03-11 المتعلق بالنقد والقرض، حيث شمل هذا القانون على عدة نقاط أساسية تهدف الى تعزيز الرقابة على البنوك والمؤسسات المالية والى تقوية السياسة الاحترازية لتحقيق الاستقرار المالي. اعتمدت هذه الدّراسة على مقابلات شبه موجّهة لمجموعة من الاطارات العاملة في البنوك الجزائرية وأساتذة في الاقتصاد. حيث خلصت هذه الدراسة الى أن القانون 23-09 سيساهم بشكل كبير في التحسين من السياسة الاحترازية لكنه غير كاف لتمكين البنوك الجزائرية من التطبيق الأمثل لمعايير بازل ،حيث يتطلب الأمر القيام باصلاح هيكلي المنظومة الاقتصادية الجزائرية. The study aims to assess Algeria's compliance with and implementation of Basel prudential standards in light of the latest reforms undertaken by public authorities in the Algerian banking sector, represented by the issuance of Banking Law No. 23-09, which repeals Banking Law No. 03-11 related to currency and credit. This law included several key points aimed at enhancing supervision of banks and financial institutions and strengthening prudential policy to achieve financial stability. This study was based on semi-directed interviews with a group of executives working in Algerian banks and economics professors. This study concluded that Law 23-09 will contribute significantly to improving the precautionary policy, but it is not sufficient to enable Algerian banks to optimally implement Basel standards, as it requires structural reform of the Algerian economic system
The reality of the precautionary policy of Algerian banks in light of the reforms to the monetary and banking law 23-09
Keywords: سياسة احترازية; معايير بازل; القانون النقدي والمصرفي; لجنة الاستقرار المالي; بنك الجزائر; Prudential Policy; Monetary and Banking Law; Financial Stability Committee; Bank of Algeria